-79=3x+7x+1

Simple and best practice solution for -79=3x+7x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -79=3x+7x+1 equation:


Simplifying
-79 = 3x + 7x + 1

Reorder the terms:
-79 = 1 + 3x + 7x

Combine like terms: 3x + 7x = 10x
-79 = 1 + 10x

Solving
-79 = 1 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-79 + -10x = 1 + 10x + -10x

Combine like terms: 10x + -10x = 0
-79 + -10x = 1 + 0
-79 + -10x = 1

Add '79' to each side of the equation.
-79 + 79 + -10x = 1 + 79

Combine like terms: -79 + 79 = 0
0 + -10x = 1 + 79
-10x = 1 + 79

Combine like terms: 1 + 79 = 80
-10x = 80

Divide each side by '-10'.
x = -8

Simplifying
x = -8

See similar equations:

| 0=-d^2+d+12 | | 2x-6-5x=6 | | 1-1-1-1-1-1-1-1-1-1-1-1-1-1-1x-2x-3-456g-a=g | | 5x-6-3x=4 | | 5x-5-6x=-6 | | 9x=8x-8 | | 2x+2x=3x+5x+1-5 | | 4-3x+5(2-x)=6(x+9) | | 5x+2-2x=8 | | 9n^2+16=-24n | | 5+5x=-50 | | 5x+-2-2x=8 | | 6(2x-1)-12=7+12(x+1) | | -0.875-(-n)=-0.583 | | m+6m+5m+8= | | 9=-5p+5+6p | | 4(2x+5)-18=36 | | -3=9p-9-8p | | (8)(16)=(6)(2x+6) | | 4=3p+6-2p | | -9x=-10x | | -3=-5p+9+6p | | 1-0.7k=1 | | -9=7p-15-6p | | 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p | | 17+9s=2(8s-3) | | 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 |

Equations solver categories